SIGNIFICANCE OF SUPPORTING CELL OF MALE GONAD IN REPRODUCTION OF FRESHWATER FISH LABEO KONTIU A SCIENTIFIC AWARENESS ABOUT REPRODUCTION - M.V. GAIKWAD,; D.K. HIWARALE,; P.M DAVNE,; J.P.SARODE,; S.L. GAIKWAD,; S.J.KAWADE,; V.R.MORE,; D.L. SONAWNE,; Y.K.KHILLARE, (International Journal of Pharma and Bio Sciences, 2011)
Reproduction is a vital process provided to all living individuals by the nature itself to reproduce their similar one after death. Labeo kontius is used due to easily throughout year availability. Male gonad was removed during different reproductive phases. The nourishing protein contain was recorded by Lowry’s method 660nm during matured male gonad as 555±1.5 mg/ml. Sertoli cells were observed on their development and parameters were recorded with the help of phase contrast microscope (Phase contrast-Olympus) as total number of Sertoli cells 15 to19 in number, diameter of the cell 0.1±0.2m perimeter of the Sertoli Cell 0.1 to 0.01m in matured testis. Same conditions were used to abnormal male brooder in hatchery the protein contain was comparatively low about infertile male brooder in matured gonad as 14.67mg/ml. The development of Sertoli cell and its parameter were comparatively low as number of Sertoli cells 9 to 12, diameter of the cell 0.5±0.1m, perimeter of the sertoli cell in male brooder. The lesser development of sertoli cell leads to improper development of Sertoli gives insufficient spem cell count for abnormal fertilization.